CO‐CBS‐H2S Axis: From Vascular Mediator to Cancer Regulator. (April 2016) - Suematsu, Makoto; Nakamura, Takashi; Tokumoto, Yasuhito; Yamamoto, Takehiro; Kajimura, Mayumi; Kabe, Yasuaki
Abstract: CO is a gaseous mediator generated by HO. Our previous studies revealed that CO generated from inducible HO‐1 or from constitutive HO‐2 modulates function of different heme proteins or enzymes through binding to their prosthetic ferrous heme to alter their structures, regulating biological function of cells and organs. Such CO‐directed target macromolecules include sGC and CBS. In the liver, CO serves as a sinusoidal dilator through its action on sGC in hepatic stellate cells, while the same gas accounts for vasoconstrictor that inhibits H2 S generated by CO‐sensitive CBS in astrocytes. Since molecular O2 is a substrate for HO, the latter mechanism contributes to hypoxic vasodilation in neurovascular units. We have recently uncovered that stress‐inducible CO in and around cancer cells suppresses CBS to result in decreased methylation of PFKFB3, the enzyme regulating PFK‐1, leading to a shift of glucose biotransformation from glycolysis toward pentose phosphate pathway; such a metabolic remodeling causes chemoresistance through increasing NADPH and reduced glutathione under stress conditions for cancer cells. This article reviews the intriguing networks of CO‐sensitive metabolic regulatory mechanisms in microcirculation and cancer.